2021
DOI: 10.1108/jhti-10-2020-0201
|View full text |Cite
|
Sign up to set email alerts
|

Linking key antecedents of hotel information management system adoption to innovative work behavior through attitudinal engagement

Abstract: PurposeThe paper aims to examine the relationship between the key antecedents of hotel information management system (HIMS) adoption and innovative work behavior (IWB) with attitudinal engagement as a mediator.Design/methodology/approachSurvey data were obtained from 297 full-time employees in five-star hotels in Uganda. With the help of Analysis of Moment Structures (AMOS), seven hypotheses were tested and analyzed using structural equation modeling (SEM).FindingsBoth perceived usefulness and perceived ease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 65 publications
(129 reference statements)
0
10
0
Order By: Relevance
“…This study also investigated and demonstrated engagement as a mediator between performance expectancy and the CUI (H10a) and between effort expectancy and the CUI (H10b); past researchers [23,24] also indicated similar results, but in general technology domains like m-BI and gaming apps. Finally, the effects of performance expectancy and effort expectancy on the CUI mediated by satisfaction (i.e., H11a and H11b) were also advocated by the current study and past analyses performed by Zhou et al [27], Rahi et al [53], and Iqbal et al [74].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This study also investigated and demonstrated engagement as a mediator between performance expectancy and the CUI (H10a) and between effort expectancy and the CUI (H10b); past researchers [23,24] also indicated similar results, but in general technology domains like m-BI and gaming apps. Finally, the effects of performance expectancy and effort expectancy on the CUI mediated by satisfaction (i.e., H11a and H11b) were also advocated by the current study and past analyses performed by Zhou et al [27], Rahi et al [53], and Iqbal et al [74].…”
Section: Discussionmentioning
confidence: 58%
“…In the field of HIMS, Omuudu et al [ 24 ] reported engagement as a significant mediator in the relationship between perceived usefulness and ease of use to innovative work behavior. Peters et al [ 20 ] confirmed the indirect effect of m-BI characteristics, including usefulness, accessibility, flexibility, and interface attractiveness, on the usage frequency via engagement.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the latter case generally happens during travel, when tourists concentrate on the destination's offering and compare it with what is being promoted when they search for the destination. Therefore, tourism managers should focus on effective promotion of the destination and providing credible information about the destination's offerings (Omuudu et al , 2022), as it creates a huge impression in tourists' minds. Because if the tourists find a huge gap between the promised and delivered service, they might get involved in the negative promotion of the destination, considering it inauthentic.…”
Section: Discussionmentioning
confidence: 99%
“…The existing hospitality literature supported the positive links between perceived ease of use, perceived usefulness, attitudes and behavioral intention in the context of new technologies (Go et al, 2020;Huang et al, 2019;Kim, 2016;Kim et al, 2008;Kim and Qu, 2014;Morosan, 2012a;Omuudu et al, 2022). Despite the wide-ranging validation of TAM in the hospitality industry, the theoretical model should be expanded across technological settings to grasp a more solid insight into new technology adoption, which can lead to a successful practical implementation (King and He, 2006).…”
Section: Introductionmentioning
confidence: 99%